2014
DOI: 10.1007/978-3-319-05119-2_12
|View full text |Cite
|
Sign up to set email alerts
|

A Library for Removing Cache-Based Attacks in Concurrent Information Flow Systems

Abstract: Abstract. Information-flow control (IFC) is a security mechanism conceived to allow untrusted code to manipulate sensitive data without compromising confidentiality. Unfortunately, untrusted code might exploit some covert channels in order to reveal information. In this paper, we focus on the LIO concurrent IFC system. By leveraging the effects of hardware caches (e.g., the CPU cache), LIO is susceptible to attacks that leak information through the internal timing covert channel. We present a resumption-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Our techniques can be adapted to other Haskell-like IFC systems beyond LIO. The library, case study, and details of the proofs can be found at [6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our techniques can be adapted to other Haskell-like IFC systems beyond LIO. The library, case study, and details of the proofs can be found at [6].…”
Section: Resultsmentioning
confidence: 99%
“…6 To consider such computations, we simply extend the definition of Thread with a new constructor: P arallel::pure b → (b → T hread m a) → T hread m a. Here, pure is a monad that characterizes pure expressions, providing the primitive runPure :: pure b → b to obtain the value denoted by the code given as argument.…”
Section: Performance Tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that this IFC mechanism could also be enforced using the hardware mechanisms we describe here. A recently proposed technique for instruction-based scheduling [17,88] is aimed at preventing leaks via the internal timing side-channel (e.g., malicious code sharing the same processor inferring secrets through timing variations arising from cache misses). This could probably be adapted to SAFE, and since the SAFE processor is very simple the mitigation could work well [24].…”
Section: Related Workmentioning
confidence: 99%
“…We believe that this IFC mechanism could also be enforced using the hardware mechanisms we describe here. A recently proposed technique for instruction-based scheduling [17,88] is aimed at preventing leaks via the internal timing side-channel (e.g., malicious code sharing the same processor inferring secrets through timing variations arising from cache misses). This could probably be adapted to SAFE, and since the SAFE processor is very simple the mitigation could work well [24].…”
Section: Related Workmentioning
confidence: 99%